A Pt–Co3O4–CD electrocatalyst with enhanced electrocatalytic performance and resistance to CO poisoning achieved by carbon dots and Co3O4 for direct methanol fuel cells. Issue 17 (20th April 2017) - Sun, Yue; Zhou, Yunjie; Zhu, Cheng; Hu, Lulu; Han, Mumei; Wang, Aoqi; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract : A Pt–Co3 O4 –CDs/C composite as an anode electrocatalyst with low Pt content exhibits superior catalytic activity, durability and anti-poisoning property for MOR. Abstract : Highly efficient electrocatalysts remain huge challenges in direct methanol fuel cells (DMFCs). Here, a Pt–Co3 O4 –CDs/C composite was fabricated as an anode electrocatalyst with low Pt content (12 wt%) by using carbon dots (CDs) and Co3 O4 nanoparticles as building blocks. The Pt–Co3 O4 –CDs/C composite catalyst shows a significantly enhanced electrocatalytic activity (1393.3 mA mg −1 Pt), durability (over 4000 s) and CO-poisoning tolerance. The superior catalytic activity should be attributed to the synergistic effect of CDs, Pt and Co3 O4 . Furthermore, the Pt–Co3 O4 –CDs/C catalyst was integrated into a single cell, which exhibits a maximum power density of 45.6 mW cm −2, 1.7 times the cell based on the commercial 20 wt% Pt/C catalyst.